Acute cervical cord syrinx after aneurysmal subarachnoid haemorrhage. (October 2016) - McAlpine, Heidi; Adamides, Alexios A.
Highlights: We report acute formation of a cervical cord syrinx after aneurysmal subarachnoid haemorrhage. Spontaneous resolution of syrinx occurred over subsequent months. This case provides further insights into the pathophysiology of syrinx formation. Abstract: We report the acute formation of a cervical cord syrinx after aneurysmal subarachnoid haemorrhage, followed by spontaneous resolution. To our knowledge, not previously described in the literature, this case provides further insights into the pathophysiology of syrinx formation, and is discussed with reference to prevailing theories.